AN ANALYSIS OF SPEECH ACT USED IN HARRY POTTER AND THE GOBLET OF FIRE MOVIE - I.A.P.A.D.P., Putri; D.P., Ramendra; I W., Swandana (International Journal of Language and Literature, 2019)
This research aimed at analyzing the speech act used in Harry Potter and the Goblet of Fire movie. This research was conducted in descriptive qualitative. The primary sources of data were utterances in Harry Potter and the Goblet of Fire movie. This research also used its movie script as a secondary source. The data were collected through observation and documentation techniques and analyzed through the stages of data reduction, data display, verification, and conclusion. The research result showed that the utterances have locutionary act or took the form of declarative, interrogative, imperative and exclamation and those were used to express the direct/indirect illocutionary act of declarative, representative, expressive, directive and commissive. Besides, the use of theforms and their illocutionary acts brought about the result of the perlocutionary acts of belief, annoyance, surprise, enlightenment, confirmation, rejection, obedience, information, happiness/satisfaction, and action. This research enriched the knowledge and understanding of the variety of structures, functions, effects, and classification of language in society.